Research on the deformation mechanism and law caused by the influence of seepage on foundation pit dewatering - Yang, Qingyuan; Chen, Song (Frontiers in Earth Science, 2025)
The thickness of aquifer is relatively large, the aquifer is not completely isolated by the diaphragm wall, and the water flow inside and outside the foundation pit flows at the bottom of the diaphragm wall. This article reports indoor experiments and theoretical methods which are used to study the deformation mechanism and law caused by dewatering in foundation pit under the condition of incomplete isolation of the inner and outer aquifers of the foundation pit based on typical geological conditions in South China. Our findings are as follows. (1) Through the experimental analysis of the mechanism of groundwater seepage around the foundation pit, the effective influence depth of precipitation in the foundation pit is greater than that outside the foundation pit, and the effective influence depth of double well precipitation is greater than that of single well precipitation. It reveals that the precipitation curve outside the foundation pit under the influence of seepage around the foundation pit presents the characteristics, and puts forward the calculation formula of surface settlement change outside the pit caused by partially penetrating well precipitation in the completely decomposed granite stratum. The calculation results of the theoretical formula are in good agreement with the experimental results, which has good accuracy and applicability. (2) The surface settlement outside the pit caused by dewatering in the foundation pit is mainly concentrated in the surrounding seepage area, and the change value of surface settlement outside the pit caused by double well dewatering is 2∼3 times greater than that caused by single well dewatering. When the whole well is vertically reinjected, the maximum surface settlement is 0.009 mm at the side near the diaphragm wall, and 0.005 mm at the side far away from the diaphragm wall. When the whole well is at an inclination of 10°, the maximum surface settlement is 0.002 mm at the side near the diaphragm wall, and 0.008 mm at the side far away from the diaphragm wall. When the whole well is at an inclination of 20°, the maximum surface settlement is −0.005 mm at the side near the diaphragm wall, and 0.011 mm at the side far away from the diaphragm wall. The full well depth recharge with an inclination of 20° has the largest influence on the surface settlement of the foundation pit, and the recharge effect is the best. (3) The lateral displacement of diaphragm wall increases by 24% compared with that without reinjection. The maximum lateral displacement of the diaphragm wall is 0.09% of the precipitation depth when the whole well is tilted at 10° for reinjection, and the lateral displacement of the diaphragm wall increases by 13% compared with that without reinjection. The maximum lateral displacement of the diaphragm wall is 0.082% of the precipitation depth when the whole well is tilted at 20° for reinjection, and the lateral displacement of the diaphragm wall increases by 4.9% compared with that without reinjection. The full well depth recharge with an inclination of 20° has the least impact on the diaphragm wall, and the recharge effect is the best. The above results can be provided as theoretical foundation for the study of the deformation mechanism and law caused by dewatering in foundation pit.